2014
DOI: 10.1038/npp.2014.292
|View full text |Cite
|
Sign up to set email alerts
|

GABAAα1-Mediated Plasticity in the Orbitofrontal Cortex Regulates Context-Dependent Action Selection

Abstract: An essential aspect of goal-directed action selection is differentiating between behaviors that are more, or less, likely to be reinforced. Habits, by contrast, are stimulus-elicited behaviors insensitive to action-outcome contingencies and are considered an etiological factor in several neuropsychiatric disorders. Thus, isolating the neuroanatomy and neurobiology of goal-directed action selection on the one hand, and habit formation on the other, is critical. Using in vivo viral-mediated gene silencing, we kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…Similarly, BALB/c mice here clearly acquired new outcome-based information as a result of contingency degradation training, even if they initially failed to inhibit responding relative to a session when responding was reinforced. By contrast, C57BL/6 mice readily inhibited responding when the only available response strategy was unlikely to be rewarded, as shown in figure 2 and previously demonstrated in other reports (Wiltgen et al, 2007;Gourley et al, 2012;Gourley et al, 2013b;Butkovich et al, 2015;Parnaudeau et al, 2015;Swanson et al, 2015). …”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Similarly, BALB/c mice here clearly acquired new outcome-based information as a result of contingency degradation training, even if they initially failed to inhibit responding relative to a session when responding was reinforced. By contrast, C57BL/6 mice readily inhibited responding when the only available response strategy was unlikely to be rewarded, as shown in figure 2 and previously demonstrated in other reports (Wiltgen et al, 2007;Gourley et al, 2012;Gourley et al, 2013b;Butkovich et al, 2015;Parnaudeau et al, 2015;Swanson et al, 2015). …”
Section: Discussionsupporting
confidence: 74%
“…During this session, reinforcers were delivered into the magazine, independent of animals’ responding, for 25 min at a rate that was yoked to each animal's individual reinforcement rate from the previous session (Gourley et al, 2012;Barker et al, 2013;Gourley et al, 2013a;Gourley et al, 2013b;Swanson et al, 2013;Barker et al, 2014;Hinton et al, 2014;Gross et al, 2015;Swanson et al, 2015;Zimmermann et al, 2015). In another session, only the opposite aperture was available, and responding was reinforced using a variable ratio 2 (VR2) schedule of reinforcement for 25 min (Baldwin et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same year, the present authors reported that oPFC-selective knockdown of Bdnf and lesions disconnecting the oPFC from the dorsal striatum also induce habits (Gourley et al, 2013a). We additionally find that habit biases can be attributed to failures in consolidating or retaining action-outcome memory (Zimmermann et al, 2015), and we have reported that viral-mediated knockdown of Gabra1 and Fmr1 in the oPFC also induce habit-based responding (Swanson et al, 2015; Gross et al, 2015). These findings suggest that the healthy oPFC is important for goal-directed (action-outcome) response selection.…”
Section: Opfc Bdnf Regulates Reward-related and Goal-directed Decisiomentioning
confidence: 89%
“…These same mice can, however, ultimately develop sensitivity to changes in instrumental contingencies with repeated training, suggesting that oPFC insult delays, but does not fully block, learning or retaining new information about action-outcome contingencies. This may also account for instances in which mice with oPFC damage fail to develop sensitivity to instrumental contingency degradation, but when tested in a reinforcer devaluation task following additional training, responding is intact (Gourley et al, 2013a; Swanson et al, 2015). Additional experiments would, however, be required to explicitly test this model.…”
Section: Opfc Bdnf Regulates Reward-related and Goal-directed Decisiomentioning
confidence: 99%